Substitution of Arginine 120 in Human D-Amino Acid Oxidase Favors FAD-Binding and Nuclear Mistargeting - Murtas, Giulia; Sacchi, Silvia; Pollegioni, Loredano (Frontiers in Molecular Biosciences, 2019)
The peroxisomal enzyme human D-amino acid oxidase (hDAAO) is attracting attention owing to its role in degrading D-serine, the main co-agonist of N-methyl D-aspartate receptors in brain, and its involvement in brain functions and diseases. Here, we focused on arginine 120, a residue located at the protein interface, 20 Å from the assumed second ligand-binding site, showing a different orientation of the side chain in the hDAAO-benzoate complex, and corresponding to Ser119 in rat DAAO, which is part of a putative nuclear translocation signal (NTS). By substituting Arg120 in hDAAO with a glutamate (to mimic the active NTS) or a leucine (to eliminate the positive charge) the protein conformation, thermal stability, and kinetic properties are slightly altered, while the dimeric structure and the ligand-binding properties are unchanged. The most relevant alteration in Arg120 variants is the strongest interaction with FAD. Nevertheless, the activity assayed at low D-serine and FAD concentrations (resembling physiological conditions) was quite similar for wild-type and Arg120 hDAAO variants. These results resemble the ones obtained substituting another residue located at the interface region (i.e., the W209R variant), indicating that substitutions at the monomer-monomer interface mainly affects the FAD binding in hDAAO. Indeed, U87 glioblastoma cells transiently transfected for hDAAO variants show that substitution of Arg120 favors mistargeting: the increase in cytosolic localization observed for the variants promotes nuclear targeting, especially for the R120E hDAAO, without affecting cell viability. Notably, mistargeting to the nucleus is an innate process as it is apparent for the wild-type hDAAO, too: whether such a process is related to specific pathologic processes is still unknown.